1970
DOI: 10.1073/pnas.67.2.1011
|View full text |Cite
|
Sign up to set email alerts
|

Polyoma „Tumor Antigen”: An Activator of Chromosome Replication?

Abstract: Abstract. We have studied the temporal relationship between the appearance of polyoma-specific "tumor antigen" and polyoma-induced activation of the cellular DNA-synthesizing apparatus in "contact-inhibited" mouse-kidney tissueculture cells. The experimental results are compatible with the hypothesis that virus-induced replication of the mouse cell chromosomes, which accompanies the actual production of progeny virus, is triggered by the tumor antigen. On the basis of the experimental evidence at present avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1971
1971
2001
2001

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…Polyoma-induced chromosome replication, however, is accompanied by the production of progeny virus and is followed by cell lysis, but not by mitosis. The results are compatible with the idea that mouse cells lack a factor(s) required for the synthesis of SV40 viral progeny DNA and for the expression of late viral functions, and that for this reason infection with SV40 remains abortive (5,14,15).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Polyoma-induced chromosome replication, however, is accompanied by the production of progeny virus and is followed by cell lysis, but not by mitosis. The results are compatible with the idea that mouse cells lack a factor(s) required for the synthesis of SV40 viral progeny DNA and for the expression of late viral functions, and that for this reason infection with SV40 remains abortive (5,14,15).…”
Section: Discussionsupporting
confidence: 78%
“…Results from studies of the relationship between the transcription of SV40-specific viral RNA and T-antigen suggest that "early" SV40-specific messenger RNAt carries (the) information necessary for the production of T-antigen (manuscript in preparation). We tentatively represent the sequential events of the abortive infection by the simplified scheme: (a) transcription of "early" virus-specific ( (14). Polyoma-induced chromosome replication, however, is accompanied by the production of progeny virus and is followed by cell lysis, but not by mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular and cytological events of the abortive infection in mouse kidney (MK) cells have been described (4,12,13). Under the conditions used in this study (10R PFU/ml; 370) a weak immunofluorescence reaction for T-antigen could be detected in 1-2% of the nuclei 7-8 hr after infection; later the relative number of positive nuclei (and the intensity of the immunofluorescence reaction) rapidly increased, reaching by 24 Under the conditions used (10P PFU/ml; 370) 1-5% of the nuclei contained T-antigen by [8][9] hr after infection; later the relative number of positive nuclei (and the intensity of the immunofluorescence reaction) rapidly increased, reaching 25-50% by 15 hr and 90-100% by [20][21][22][23][24] hr after infection. Time course of infection was similar in confluent BSC and Vero monkey kidney cell lines and also in confluent primary monkey kidney cell cultures.…”
Section: Resultsmentioning
confidence: 99%
“…However, in mixed incubation experiments, the molecular weight of T-antigen remains 86,000 not only in MK cell extracts, but also in the presence of extracts of other kinds of nonpermissive cells derived from the hamster. Earlier observations suggested that SV4O-(and polyoma-) induced host chromatin replication may be necessary but is not sufficient for viral DNA replication; hence it was postulated that permissive cells may contain a specific factor(s) absent in nonpermissive cells (4,23). Without proving it, our results are compatible with the hypothesis that this factor is a protease(s): 86 kDal T-antigen synthesized in nonpermissive cells would be able to induce a mitogenic response (leading to chromatin replication and mitosis), but it would allow autonomous replication of the viral DNA only if cleaved to the 82 kDal form.…”
Section: Identification Of the Polypeptides By Fingerprinting Analysismentioning
confidence: 99%
“…"Py-induced cellular DNA synthesis is neither preceded nor accompanied by an overall stimulation of cellular RNA synthesis nor is it followed by mitosis" (261) Py infection of highly confluent cells in culture has been frequently reported to stimulate an unscheduled round of cellular DNA synthesis (96,372,373). This synthesis, however, may occur out of normal cell cycle control, and it does not involve a full round of the cell cycle since mitosis does not follow the S phase (197,198).…”
Section: Dna Synthesismentioning
confidence: 99%